Pemalsuan dalam Penerbitan Sertipikat Hak Guna Bangunan sebagai Tindak Pidana Korupsi - Engelin Kamea; Rena Yulia; Dadang Herli S (Universitas Muhammadiyah Yogyakarta, 2024)
This research is motivated by the many cases of issuance of Building Rights Title certificates on land that was never obtained by legal means. The issuance of these certificates occurs because of abuse of authority by civil servants at the land office. The purpose of this study is to determine the application of the Corruption Eradication Law and the authority of the prosecutor's office in cases of forgery in the issuance of Building Rights Title certificates. This research is a normative legal research with statute approach and case approach. The results of this study found that the application of the Corruption Eradication Law in cases of forgery in the issuance of Building Use Rights Certificates can be done by looking at the elements of the criminal act contained in Article 9 of Law No. 20 of 2001 concerning Amendments to Law No. 31 of 1999 concerning Eradication of Corruption. 31 of 1999 on the Eradication of the Criminal Act of Corruption, namely: civil servants or persons other than civil servants who are assigned the task of carrying out a public office continuously or temporarily, deliberately falsifying books or lists specifically for administrative examination, then the authority of the prosecutor's office in cases of forgery in the issuance of Building Rights Title Certificates, lies in the position of the prosecutor's office as a sub-system that has the authority to investigate, prosecute and implement court decisions.